(untitled) (Ameghiniana, 2013)
ABSTRACT: "GEOLOGY AND PALAEONTOLOGOY OF THE PLEISTOCENE SEDIMENTS AT PUNTA HERMENGO AREA (MlRAMAR,BUENOS AIRES PROVINCE,ARGENTINE REPUBLIC): PALAEOCLIMATIC ASPECTS".- A profile of sedimentary deposits, with a mean thickess of 5 m, is described. Seven "sectors" have been differentiated in the profile, which are limited by erosional surfaces and/ or discontinuities. The sediments studied in this profile grade from sandy silts to clayey silts. Calcium carbonate hardpan (locally named "tosca") appears throughout all the profile in various shapes and sizes (veins, beds, dolls and angular to rounded clasts). Sometimes, crossbedding (planar or trough) has been observed in these sediments, though much more frequently in those with a higher sand contento Field observations have been done along a 3 km long costal cliff, south of Punta Hermengo. However, most characteristics observed here are common in fue "pampean sediments" of many other localities in Buenos Aires province. For instance, "tosca" appears almost everywhere though it increases its surficial abundance and complexity from NE (Buenos Aires city) to SW and W (Bahía Blanca and La Pampa province, respectively). The vertebrate fossil fauna found within profile "sectors" B, D and G, includes: (a) Aves: sp., seus cf. gonus, Psittacidae sp. indet. 1, Psittacidae sp. indet. 2, Col pest (b) Mammalia: estodelphis cf. , o sp., e s cf. pichi , eutes cf. . p eu s cf. seguini, c c i s, c oc sp., ostoi , gosto s sp., Cteno s sp., itus, o s sp., c ist li leptoceph , Equus s) sp., ptodon cf. cl ipes. Based on the available geological and palaeontological data, it is concluded that: 1) The Punta Hermengo profile sediments extend from Mid to Late Pleistocene in age, i.e., Ensenadan and Lujanian Mammal-Ages. 2) Most of the outcropping sediments were probably deposited under arid to semi-arid clima tic conditions. This is suggested by oligomictic diamicttes, massive siltstones and K-soils horizons (petrocalcic soils). The region was inhabited at this time by a bird- and mammal fauna belonging to Patagonian and Central "stocks" but not to the Subtropical "stock" as in the present-day distribution. 3) More humid conditions may be suggested by (a) coarsely-stratified silty sediments, (b ) lenses of rounded to subrounded "tosca" clasts whích were deposited in channel-like depressions, and (c) soil horizons with high clay concentration and dark or black cutans. 4) It .seems likely that arid and semi-arid conditions were accompanied by a general lowering in mean annual temperatures, which at lowermost levels favoured the expansion of Patagonian faunas and at highermost levels induced the distribution of Central and Pampean faunas, being the latter similar to the present living one.5) The absence of articulated fossil skeletons and the existence of diamictitic deposits suggest that erosion-and-transport processes were very signíficant at some moments. landscape was similar to the present one, though with different climatic conditions. These evidences, together with the faunal analysis, seem to indicate the existence of relatively homogeneous open-space habitats. 7) These remarkable faunal variations were driven by dramatic climatic changes which are probably related with glacial and interglacial epochs. This hypothesis has already been proposed for the Uppermost Pleistocene and Holocene deposits of Buenos Aires province, thus including the latest Great Glaciation and the present Interglacial. Thus, it seems clear that pre-Wisconsinan glacial epochs are represented in the deposits of Punta Hermengo profile.